Directional copper dewetting to grow graphene ribbon arrays. Issue 99 (29th November 2021) - Li, Xiaogang; Xiong, Xuyao; Ning, Congcong; Yang, Qian; Li, Dongling; Wang, Zegao; Jin, Yan; Zhao, Wenbin; Hu, Baoshan
Abstract : A novel strategy that employs V-shaped grooves to confine the directional dewetting of a Cu film facilitates the CVD growth of graphene ribbons. Abstract : The V-groove confines the anisotropic dewetting of Cu film to form ribbons. The influence mechanism of film thickness and annealing procedure on the confined dewetting, structural and morphological evolution has been investigated. Thus, the synthesized graphene ribbons by CVD have uniform width, regular edges and good crystallinity, and deliver obvious room-temperature PL emission.